2015
DOI: 10.1111/cei.12645
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effect of combined complement and CD14 inhibition is preserved during escalating bacterial load

Abstract: SummaryCombined inhibition of complement and CD14 is known to attenuate bacterial-induced inflammation, but the dependency of the bacterial load on this effect is unknown. Thus, we investigated whether the effect of such combined inhibition on Escherichia coli-and Staphylococcus aureus-induced inflammation was preserved during increasing bacterial concentrations. Human whole blood was preincubated with anti-CD14, eculizumab (C5-inhibitor) or compstatin (C3-inhibitor), or combinations thereof. Then heat-inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Genetic ablation or pharmacological blockade of C5a signalling or C3 activation improves outcomes in animal models of sepsis 81,83,84 . Moreover, in vitro and in vivo studies have provided evidence of synergistic effects of blocking complement and TLRs simultaneously 85,86 , underscoring the crosstalk that occurs between these systems in pathological events. In patients with severe trauma, the presentation of DAMPs after tissue injury can trigger complement activation, which induces SIRS and contributes to complications such as multi-organ dysfunction and/or death 8789 .…”
Section: Complex Involvement In Clinical Disordersmentioning
confidence: 99%
“…Genetic ablation or pharmacological blockade of C5a signalling or C3 activation improves outcomes in animal models of sepsis 81,83,84 . Moreover, in vitro and in vivo studies have provided evidence of synergistic effects of blocking complement and TLRs simultaneously 85,86 , underscoring the crosstalk that occurs between these systems in pathological events. In patients with severe trauma, the presentation of DAMPs after tissue injury can trigger complement activation, which induces SIRS and contributes to complications such as multi-organ dysfunction and/or death 8789 .…”
Section: Complex Involvement In Clinical Disordersmentioning
confidence: 99%
“…We found that E. coli-induced whole blood-mediated activation of EC was largely CD14-dependent whereas S. aureus-induced activation was mediated by the complement system, mainly through C5a-C5aR1 interaction. We have earlier found that single inhibition is less efficient than combined inhibition, particularly with increased load of inflammatory stimuli (35). In the present study, we used fairly low concentrations of bacteria compared with previous studies in whole blood alone, which might explain the impressive effect of single inhibition.…”
Section: Discussionmentioning
confidence: 86%
“…For instance, congruently upregulated genes included the CD14 molecule, the lipopolysaccharide‐binding protein (LBP), and the Toll‐like receptors (TLRs) 2, 4, 6, and 8. CD14 is an accessory receptor for TLRs, and ongoing clinical trials indicate that CD14 inhibition is a promising strategy to treat sepsis (Verbon et al , ; Egge et al , ). Furthermore, LBP is an acute‐phase biomarker for sepsis (Schumann & Zweigner, ), and the TLR family was recently reported to be a promising target for the treatment of sepsis (Savva & Roger, ).…”
Section: Discussionmentioning
confidence: 99%